The fall of the house of Dixie : the Civil War and the social revolution that transformed the South - Levine, Bruce C., 1949- (Random House, 2013)
In this major new history of the Civil War, Bruce Levine tells the riveting story of how that conflict upended the economic, political, and social life of the old South, utterly destroying the Confederacy and the society it represented and defended.